Pain is inevitable, suffering is optional: The effect of stress on pain tolerance - Nurwanti, Ratri; Qonita, Sarah (Universitas Brawijaya, 2025)
Stress and pain tolerance are known to have a causal and even a circular causality relationship. However, current evidence shows contradictory results. Researchers believe that stress could reduce pain tolerance, yet others believe the opposite. These differences among studies might relate to the instrument or protocol differences, only involving either men or women as participants and participants' condition (patient versus non-patient). This randomized between-subject experimental study investigated the effect of stress induction on pain tolerance involving healthy men and women as participants. A total of 40 participants were randomly assigned to either the experimental condition, where they received stress induction using the Trier Social Stress Test (N = 17), or the control condition, where they received the placebo task of the friendly-Trier Social Stress Test (N = 23). We also used the Cold Pressure Test (CPT) protocol to measure pain tolerance. The main analysis of this study showed that moderate and short stress resulting from stress induction significantly reduced participants’ pain tolerance. Despite the significant pain tolerance difference between the experimental and control condition, participants in both groups rated the pain they experienced at the same intensity. A correlational analysis between pain intensity and pain tolerance showing a significant negative correlation between those variables supported this finding. This complex mechanism of stress and pain tolerance needs further study and exploration.